Renal vein stenting abates sickle cell trait mediated chronic refractory hematuria exacerbated by the Nutcracker phenomenon - Naiem Nassiri; Lauren A. Huntress; Sammy Elsamra; Susan Murphy; Yi-Horng Lee (Elsevier, 2017)
Nutcracker syndrome (NCS) is a rare vascular anomaly involving left renal vein (LRV) outflow entrapment most commonly between the aorta and the superiormesenteric artery (SMA). This can lead to chronic LRV hypertension with resultant gonadal vein reflux, pelvic varicosity formation, hematuria, anemia, failure to thrive, and if severe enough, renal failure. Sickle cell trait (SCT) is a well-known and relatively common cause of hematuria causing damage to the renal microvasculature with subsequent renal papillary necrosis. In the rare setting of both conditions, LRV compression exacerbates upstream LRV sickling and exponentially augments hematuria. As is presented here, alleviation of LRV compression via a minimally endovascular approach can cease life-threatening hematuria.